Pengaruh Penggunaan Minuman Berkarbonasi Untuk Menghambat Kemunduran Mutu Ikan Gurami (Osphronemus gouramy) Pada Suhu Kamar - Jayanti, Siska; Ilza, Mirna; ', Desmelati (Fakultas Perikanan dan Kelautan Universitas Riau, 2012)
This research was conducted at the Laboratory of Technology of Processing,Chemical Fisheries and Fishery Microbiology Faculty of Fisheries and MarineSciences University of Riau, in October 2011. The research objective was todetermine the effect of addition carbonated water on freshness quality of Carpstored at room temperature. Carp weighing ± 200 grams each was obtained from afish market in Pekanbaru. The fish was grouped into 2 groups. First group wassoaked in 10% carbonated water and another group was soaked in 3.2%carbonated water +3.2% sugar +5.8% natrium. After soaking for 30 minutes, thefish was stored at room temperature for 12 hours. Fish quality was evaluated forsensory atribute, pH, TPC and TVB. The results showed that the fish added with10% carbonated water had a longer shelf life than those soaked in 3.2%.